1976
DOI: 10.1111/j.1432-1033.1976.tb09998.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Role and Mode of Operation of the Very-Lysine-Rich Histone H1 in Eukaryote Chromatin. The Isolation of the Globular and Non-Globular Regions of the Histone H1 Molecule

Abstract: Digestion of calf thymus H1 histone with thrombin cleaves the molecule at the sequence -(Pro)-Lys-Lys-Ala-, corresponding to a point approximately 122 residues from the N-terminus (about 56% along the molecule). The N-terminal fragment is shown by proton nuclear magnetic resonance (NMR) to possess the globular structure of the intact histone HI molecule, whereas the C-terminal fragment appears to possess little or no structure. The N-terminal fragment separates into two peaks on an ion-exchange column, one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…There are parallels in this respect with thymus HI histones Fig. 8 NMR spectru of recombined complex between high-mohilrtv-group protein 1 ( 3 ntgiml) and DNA (6 mg/ml) in 'H,Ol NaCI, pH 6 9, 20 C, and (above) equivalent spectra of protein alone ( 3 mglml) in 'H,O/NUCI, pH 6 9, 20 C that also forms a globular structure (on increase of pH from 3-6, or by salt addition at acid pH) that involves, at maximum only about one half of the 216 residues in H1 [7,8,13]. In the case of the highmobility-group proteins, lack of sequence data prevents any firm statements on the size of the globular segment, but the general conclusion remains that conformationally the high-mobility-group proteins resemble most closely the lysine-rich histones H1 and H 5, with the exception that the high-mobility-group proteins show aggregation at neutral pH whereas H 1 and H 5 do not.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are parallels in this respect with thymus HI histones Fig. 8 NMR spectru of recombined complex between high-mohilrtv-group protein 1 ( 3 ntgiml) and DNA (6 mg/ml) in 'H,Ol NaCI, pH 6 9, 20 C, and (above) equivalent spectra of protein alone ( 3 mglml) in 'H,O/NUCI, pH 6 9, 20 C that also forms a globular structure (on increase of pH from 3-6, or by salt addition at acid pH) that involves, at maximum only about one half of the 216 residues in H1 [7,8,13]. In the case of the highmobility-group proteins, lack of sequence data prevents any firm statements on the size of the globular segment, but the general conclusion remains that conformationally the high-mobility-group proteins resemble most closely the lysine-rich histones H1 and H 5, with the exception that the high-mobility-group proteins show aggregation at neutral pH whereas H 1 and H 5 do not.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in the pH from 3-7 does not by itself induce large structural changes in the conformation of these four histones but this is not found to be the case with H1 which is observed to form both secondary and tertiary structure on pH increase without any concomitant aggregation [7]. At neutral pH (or at pH 3 in high salt) H1 therefore behaves like a single subunit globular protein with the notable difference that only about half of the molecule is included in the fold [8]. The availability of milligram quantities of the high-mobility-group proteins led us to the present structural studies and we have concluded that conformationally they are capable of forming globular structures with specific secondary and tertiary folds.…”
mentioning
confidence: 99%
“…Thus they either represent different subfractions cut at the same point in the chain and/or a small amount of C-terminal loss. Although it is often thought (on the basis of partial sequence data) that HI subfractions differ most characteristically at the N-terminus, it is found that the peptide mixture generated by thrombin digestion (Chapman et al, 1976) (which represents residues 122 to the Cterminus from a mixture of fractions) consists of peptides with a wide spread of mobilities. The two peptides of the B IV mixture could both be intact at the C-terminus.…”
Section: Methodsmentioning
confidence: 99%
“…86 residues in calf thymus HI) and a long unstructured C-terminal domain of very basic composition comprising almost half the molecule (approx. 93 residues in calf thymus HI) (Chapman et al, 1976;Hartman et al, 1977;Puigdomenech et al, 1980;Barbero et al, 1980;Aviles et al, 1978). By reconstituting several HI peptides on to chromatin depleted of its original Hi, it was shown that the central globular domain alone is able to close two full turns of nucleosomal DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation